RETRACTION NOTICE "ASSESSING THE PARTICIPATION OF WOMEN IN THE PRODUCTION OF LARGE CARDAMOM IN THE ILAM DISTRICT OF NEPAL" - Gotame, Mahima; Santosh, B K (Agricultural Socio-Economics Journal, 2023)
This article has been retracted by the publisher. ----------------------------------------------------------------------- This article has been retracted at the request of the Authors. The editors and authors have jointly made the decision to retract the paper. Reasonable effort should be made to remove references to this paper. -----------------------------------------------------------------------